Tfhe Death penalty and the absolute prohibition of torture and cruel, inhuman and degrading treatment or punishment - Méndez, Juan E. (2012)
Examines the growing trend in international law to frame the debate about the legality of the death penalty within the context of the prohibition of torture and cruel, inhuman and degrading treatment or punishment (CIDT).